Nigella sativa protects against isoproterenol-induced myocardial infarction by alleviating oxidative stress, biochemical alterations and histological damage - Md. Quamrul Hassan; Mohd. Akhtar; Sayeed Ahmed; Aftab Ahmad; Abul Kalam Najmi (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To evaluate the cardioprotective effect of Nigella sativa L. (N. sativa) in isoproterenol-induced myocardial infarction (MI). Methods: Groups were treated with different doses of ethanol extract of N. sativa (EENS) and N. sativa oil alone and along with enalapril for 28 days. MI was induced by subcutaneous administration of isoproterenol (85 mg/kg) in two consecutive doses. Levels of cardiac biomarkers and antioxidant enzymes such as creatine kinase–N-acetyl-l-cysteine, lactate dehydrogenase, aspartate aminotransferase, malondialdehyde, superoxide dismutase, reduced glutathione and catalase were evaluated along with gross histopathological examination. Results: Isoproterenol (85 mg/kg) induced MI by causing the significant (P < 0.01) reduction in the activity of cardiac biomarkers (creatine kinase–N-acetyl-l-cysteine, lactate dehydrogenase, aspartate aminotransferase) and antioxidant markers (superoxide dismutase, catalase, glutathione) along with significant (P < 0.01) increase in the level of malondialdehyde. Furthermore, histopathological evaluation also confirmed the isoproterenol-induced MI. Pretreatment with EENS (800 mg/kg) and combination of EENS (800 mg/kg) with enalapril (1 mg/kg) significantly (P < 0.01) prevented the development of these alteration and restored activity of cardiac biomarkers as well as antioxidant markers almost near to normal levels. Histopathological evaluation of cardiac tissue further confirmed the restoration of biochemical activity. Conclusions: Experimental findings thus indicate that EENS (800 mg/kg) demonstrated cardioprotective effect against isoproterenol-induced MI by restoring cardiac biomarkers and antioxidant status.